Disaster Rights: Public and Private Responsibility in Safeguarding Human Rights during Environmental Disasters - Flávia Jeane Ferrari; Viviane Coêlho de Séllos-Knoerr; Antonio Evangelista de Souza Netto (Centro Universitário Adventista de São Paulo, 2023)
Objective: This research aims to examine the construction of Disaster Law, focusing on the allocation of responsibility to private entities and its correlation with Human Rights, Business Law, and Environmental Law spheres. The study intends to clarify the emerging inclusion of human rights, business law, and environmental law as indispensable aspects within the realm of Disaster Law. Method: The research adopts a dialectical method, employing bibliographic and normative analysis to elucidate the integration of human rights, business law, and environmental law as essential components in Disaster Law. Existing documents from international agencies and programs that encompass the legal aspects of environmental disasters will be examined and analyzed to achieve the research objectives. Results: The analysis will shed light on the premises of Disaster Law in alignment with environmental rights and human rights. The research seeks to initiate discussions on the development of a comprehensive legal framework for disasters, encompassing responsibilities of both public and private entities, with the aim of safeguarding inherent human rights. Conclusions: The urgent need for discussions on the establishment of Disaster Law, holding both public and private entities accountable, and ensuring the protection of human rights justifies the significance of this research. By exploring the interconnections between Disaster Law, Human Rights, Business Law, and Environmental Law, this study contributes to the construction of a comprehensive legal framework that addresses the challenges posed by environmental disasters.